An Empirical Study of Quick Ratio and Profitability on Manufacturing Firms in Indonesia - Pandeirot, Lanemey Brigitha; Sumanti, Elvis Ronald; Aseng, Andrew Christian (Society, 2022)
This study intended to test the effect of the quick ratio on manufacturing firms’ profitability in Indonesia. To measure the profitability, three dependent variables were used: Net Profit Margin (NPM), Return On Assets (ROA) and Return On Equity (ROE). Several variable controls were used: firm size, variability in net operating income, sales growth, gross domestic product growth, and leverage. A total of 158 manufacturing firms with published financial statements from 2012 to 2016 were analyzed using a regression method. It is found that quick ratio has positive effects on manufacturing firms’ NPM and ROA. However, the same effect is not found on ROE.